Fatliquoring process on tuna fish skin tanning for the shoe upper leather. Issue 1 (April 2020) - Suparno, O; Saputra, A
Abstract: Fatliquoring is a part of tanning process, which is penetrating the fatliquoring agent into leather's empty cells. The process changes the physical characteristics of leather, which make it softer, more elastic, flexible, and give smooth grain surface. This study is conducted to investigate the effects of type and dosage of fatliquors on the physical properties of tuna skin leather for the shoe upper. The types of fatliquors used are natural and synthetic, and the dosages are 3%, 6%, 9%, 12%, and 15%. Thickness increase, tear strength, tensile strength, elongation at break, and organoleptic properties of the leather are investigated. Based on this study, the types of fatliquor significantly affect the tear strength and elongation at break. The dosages of fatliquor which are nested in the type of fatliquor significantly affect tear strength, tensile strength, and elongation at break. The best treatment in this study is synthetic fatliquor with dosage of 3%. The treatment produced leather with thickness increase of 32.4%, tear strength of 95.3 N/mm, tensile strength of 27.9 N/mm 2, elongation at break of 45.3%, dark brown colour, smooth feel or handle, and good flexibility.